MODÉL STUDENT TEAM ACHIEVEMENT DIVISION (STAD) PIKEUN NGARONJATKEUN KAMAMPUH NULIS PUPUH : Studi Kuasi Ekspérimén Siswa Kelas VIII B SMP Negeri 27 Bandung Taun Ajaran 2017/2018 - Hakim, Rifal Lukmanul (2017)
The background of this research is the lack of students ability in learning writing Pupuh. This study is expected to determine students skills in writing Pupuh, before and after using the model Student Team Achievement Division (STAD). The method used in this study is quasi-experimental methods. The Resource of this research is student of VIII B junior high School of 27 Bandung academic year 2017/2018totally is 39 people, they are 19 students of male and 20 students of female. The technique used in this study is technique of testing, with booklet written instrument. Based on the results of the study, the average value of wrote Pupuh VIII B junior high School of 27 Bandung academic year 2017/2018before using STAD learning model is (52.79) has not been able to reach KKM goals, while the average value writing Pupuh after use STAD learning model (76,79) has been able to achieve KKM goals. It can be seen from the results of hypothesis testing is tcout (11,59)> ttable (2,42). This proves that the model of Student Team Achievement Division (STAD) can improve the ability to write Pupuh in VIII B junior high School of 27 Bandung academic year 2017/2018----- Latar belakang dalam penelitian ini adalah kurangnya kemampuan siswa dalam pembelajaran menulis pupuh. Penelitian ini bertujuan untuk mengetahui kemampuan siswa dalam menulis pupuh, sebelum dan sesudah menggunakan model Student Team Achievement Division (STAD). Metode yang digunakan dalam penelitian ini adalah metode kuasi eksperimen. Sumber data dalam penelitian ini adalah siswa kelas VIII B SMP Negeri 27 Bandung tahun ajaran 2017/2018 yang berjumlah 39 orang, 19 siswa laki-laki dan 20 siswa perempuan. Teknik yang digunakan adalah teknik tes, dengan istrumen lembar soal tertulis. Berdasarkan hasil penelitian, nilai rata-rata menulis pupuh siswa kelas VIII B SMP Negeri 27 Bandung sebelum menggunakan model pembelajaran STAD yaitu (52,79) belum mampu mencapai KKM, sedangkan nilai rata-rata menulis aksara Sunda sesudah menggunakan model pembelajaran STAD (76,79) sudah mampu mencapai KKM. Hal tersebut bisa dilihat dari hasil uji hipotesis yaitu thitung (11,59) > ttabel (2,42). Hal ini membuktikan bahwa model Student Team Achievement Division (STAD) dapat meningkatkan kemampuan menulis pupuh siswa kelas VIII B SMP Negeri 27 Bandung tahun ajaran 2017/2018